The role of home and childcare chaos in children’s development - Eroğlu Ada, Figen. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
The present study investigated the additive and interactive roles of home and childcare chaos in predicting preschool children’s social competence and adjustment, effortful control, and emotionality. The participants of the study consisted of 269 (137 boys, 132 girls) preschoolers, their mothers and preschool teachers. Home and childcare chaos were measured through mother report of CHAOS and teacher report of LECP scale, respectively. The additive and interactive roles between the home and childcare chaos were tested by using multilevel linear model analyses. The additive role of home and childcare chaos was documented only in the prediction of externalizing problems. In the case of internalizing, only home chaos, and in the case of social competence, only childcare chaos accounted for significant variation. However, the two-way interaction term between the home and childcare chaos was not significant in predicting any of the child developmental outcomes. In other words, the relationship between chaos in one context and child development was not moderated by the chaos in the other context. Besides, children who were exposed to double jeopardy (i.e., high levels of home and childcare chaos) were investigated by using triadic splits on the distribution of home and childcare chaos. Children in this group displayed more externalizing problems than children who were in the double protection group (i.e., low levels of home and childcare chaos). Also, children from low-chaos home environments, but high-chaos childcare environments displayed less social competence than those experiencing average levels of chaos in both contexts. These findings suggest policies focusing on the additive role of risky settings.
Keywords: Child development.; Chaos.